2021
DOI: 10.3389/fpls.2021.727741
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protein Expression Analysis of Two Sugarcane Varieties in Response to Diazotrophic Plant Growth-Promoting Endophyte Enterobacter roggenkampii ED5

Abstract: Plant endophytic bacteria have many vital roles in plant growth promotion (PGP), such as nitrogen (N) fixation and resistance to biotic and abiotic stresses. In this study, the seedlings of sugarcane varieties B8 (requires a low concentration of nitrogen for growth) and GT11 (requires a high concentration of nitrogen for growth) were inoculated with endophytic diazotroph Enterobacter roggenkampii ED5, which exhibits multiple PGP traits, isolated from sugarcane roots. The results showed that the inoculation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…At the same time, it was found that the activities of oxidative stress enzymes (SOD, POD, and CAT) and the content of oxidative product MDA in sugarcane varieties, GT11 and B8, inoculated with the DJ06 strain was significantly changed as compared with the controls in this study, indicating that the DJ06 strain stimulated the occurrence of physiological responses of sugarcane, and then enhance the ability to adapt to the external environment. The variations in SOD, POD, and MDA activities after inoculation of the DJ06 strain may differ from the genetic variability in the two sugarcane varieties (Guo et al, 2021 ). In addition, this study found that there were mobile genetic elements (MGEs) in the genome of the DJ06 strain, such as the CRISPR system and prophage, which play an important role in PGPB strains for adaptation to the environment, and similar results were also reported in Enterobacter roggenkampii ED5 (Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it was found that the activities of oxidative stress enzymes (SOD, POD, and CAT) and the content of oxidative product MDA in sugarcane varieties, GT11 and B8, inoculated with the DJ06 strain was significantly changed as compared with the controls in this study, indicating that the DJ06 strain stimulated the occurrence of physiological responses of sugarcane, and then enhance the ability to adapt to the external environment. The variations in SOD, POD, and MDA activities after inoculation of the DJ06 strain may differ from the genetic variability in the two sugarcane varieties (Guo et al, 2021 ). In addition, this study found that there were mobile genetic elements (MGEs) in the genome of the DJ06 strain, such as the CRISPR system and prophage, which play an important role in PGPB strains for adaptation to the environment, and similar results were also reported in Enterobacter roggenkampii ED5 (Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The coding sequence (CDS), tRNA, and rRNA were predicted by Glimmer 3.02, tRNAscan-SE 2.0, and Barrnap software, respectively. The predicted CDS protein functions were annotated from NR, Swiss prot, Pfam, Gene Ontology (GO), Clusters of Orthologous Groups (COG), and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases by using Blast2go 2.0, Diamond 0.8.35, HMMER3.1b2, and other sequence alignment tools (Guo et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…are recognized as human pathogens ( 2 ), E. roggenkampii represents only around 4% of clinical ECC isolates ( 3 6 ). Commonly associated with plants ( 7 , 8 ), it has been proposed for crop growth promotion ( 9 ), although its versatile biochemistry includes broad intrinsic antimicrobial resistance ( 10 ) and the ability to hasten the corrosion of steel ( 11 ). As endophytes and in the rhizosphere, isolates of E. roggenkampii may produce indole-3-acetic acid and siderophores, solubilize phosphate, and fix nitrogen ( 7 , 12 ).…”
Section: Announcementmentioning
confidence: 99%
“…The beneficial impacts of the endophytic bacteria on host plants are usually greater than those provided by many rhizosphere bacteria. They can benefit host plants directly by improving plant nutrient uptake ( Guo et al., 2021 ) and modulating growth and stress-related phytohormones ( Nivedita et al., 2020 ; Cipriano et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%